'It's music and we came to play instruments': teaching for engagement in classroom music. (8th August 2022) - Wilson, Emily
ABSTRACT: This paper presents findings from ethnographic case study research that investigated teacher practices and student engagement in classroom music. The data collection was undertaken in a primary (elementary) and a secondary school in Australia and focussed on the classroom practice of two teachers and four classes of students aged 10 to 16 years. The two teachers invited to participate in the study had been identified as being influenced by the Musical Futures approach following their participation in a Musical Futures professional learning workshop. The findings draw on participant-observation of music lessons, interviews, and focus groups. From this research, a model of teaching for engagement in classroom is proposed. This paper discusses three over-arching themes that comprise the model, illustrated with classroom snapshots from secondary Year 10 and Year 7 music classes and primary Year 5/6 music classes.